Overview of COVID-19 mortality in Zoram Medical College, Mizoram: A hospital-based study - C Laltlanzovi; C Vankhuma; Vanlalduhsaki; Diana Lalrinsiami Chhakchhuak; J.C. Zothanzauva (Journal of Family Medicine and Primary Care, 2023)
Background: Mizoram is a small state in the northeastern part of India and recorded its first case of coronavirus disease 2019 (COVID-19) on March 24, 2020. The first registered death because of COVID-19 in the state was on October 28, 2020 at Zoram Medical College (ZMC), which is a dedicated COVID hospital in Mizoram. COVID-19 cases from different districts in the state were referred to ZMC according to severity of symptoms. NCDIR-ICMR e-Mortality Cell was first started as a project at ZMC in 2019. Since then, all hospital deaths are recorded using a structured questionnaire developed by NCDIR which has also strengthened the data for COVID-19 mortality statistics in the state. The objective of this study is to determine the association of in-hospital COVID-19 mortality in relation to age, sex, vaccine status, and underlying co-morbidities and highlight the utility of ICMR-NCDIR e-Mortality software in the hospital. Methods: Data on COVID-19-associated deaths from October 2020 to October 2021 at ZMC were collected from the hospital e-Mortality software and Medical Records Department (MRD). This includes patients’ demographic characteristics including age, sex, vaccination status, and underlying co-morbidities if any. Appropriate statistical analysis was performed to evaluate the correlation between variables. Results: From October 2020 to October 2021, a total of 324 deaths related to COVID-19 was recorded at ZMC, Mizoram. The majority of the deaths were distributed in the age group 65 years and above and accounts for 49.1% in all age groups. Out of the total deaths, 64.2% (208) were males and 81.48% had an associated underlying co-morbidity besides COVID-19. The most common co-morbidities were hypertension, type 2 diabetes mellitus, cancer, and chronic obstructive pulmonary disease. More than half, 59.6%, had no vaccination history, and all the cases had no history of taking a booster vaccination dose. A statistically significant correlation between delay in time to admission and length of hospital stay (p = 0.017) was also seen. Conclusions: COVID-19 is more severe in the older age group above 65 years of age and in males, particularly in the presence of underlying co-morbidities. Mortality was also higher in patients with no history of vaccination as compared with patients vaccinated. Also, delay in hospital admission increases the length of hospital stay and mortality.